2006
DOI: 10.1542/peds.2005-2948
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined Effects of Postpartum Depression in Mothers and Fathers on Parenting Behavior

Abstract: Postpartum depression is a significant problem in both mothers and fathers in the United States. It is associated with undesirable parent health behaviors and fewer positive parent-infant interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
427
5
23

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(464 citation statements)
references
References 46 publications
9
427
5
23
Order By: Relevance
“…A recent study showed an optimal cut-off score at ≥ 13 for detecting depressive symptoms during pregnancy used in primary health care (Rubertsson, 2011). Another Swedish study described that an EPDS score of [9][10][11] indicates high levels of stress, marital problems and perceived child difficulties [23].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed an optimal cut-off score at ≥ 13 for detecting depressive symptoms during pregnancy used in primary health care (Rubertsson, 2011). Another Swedish study described that an EPDS score of [9][10][11] indicates high levels of stress, marital problems and perceived child difficulties [23].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In both mothers and fathers, post-partum depression is negatively associated with positive enrichment activities with the child such as singing and reading [9]. The demands on a new parent to care for a child and manage household tasks can be difficult to bear in normal circumstances and are exacerbated by the disability associated with depressive symptoms [1].…”
Section: Introductionmentioning
confidence: 99%
“…Results from Poisson regression analysis, involving all risk factors identifi ed as associated with the outcomes in the bivariate analysis, showed maintenance of the association between two risk factors: mother's lack of involvement with work outside the home and the couple 19 is surprising, the fi ndings are coherent. Social expectations observed in the community are characterized by traditional gender relations, with strict role division between parents, where women are destined to care for the home and children, whereas men are destined to support the family and care for the family customs and values.…”
Section: Discussionmentioning
confidence: 96%
“…1,7,11,21 Despite their lack of statistical signifi cance, the variables "low level of education" and "presence of father and mother mental disorder" show prevalence ratios that must be taken into consideration, once they are factors usually regarded as associated with parent-child relationship quality, revealing damage to the fatherinfant relationship. 19 The present study enabled the direct observation of family groups of all children born in a certain district at a particular time, as well as their interactions in their environment. Moreover, a research instrument scoring method with consensus of two observers was employed, thus minimizing possible measurement bias.…”
Section: Discussionmentioning
confidence: 98%
“…The Agency for Healthcare Research and Quality estimates that the prevalence of depression during pregnancy ranges from 8.5% to 10.0% and during the first postpartum year it ranges from 6.5% to 12.9% (Gaynes et al, 2005). The actual prevalence of postpartum depression may be higher as diagnostic criteria vary among health care disciplines (Beck & Driscoll, 2006;NIMH, 2009;Paulson et al, 2006).…”
Section: Female Caregiver Characteristicsmentioning
confidence: 99%